2013
DOI: 10.5173/ceju.2013.03.art2
|View full text |Cite
|
Sign up to set email alerts
|

Original Paper Inflammatory changes in biopsy specimens from patients with suspected prostate cancer

Abstract: IntroductionProstate cancer (PCa) is one of the most commonly diagnosed cancers in elderly men, and accounts for 30% of all newly diagnosed cases of cancer. The development of the ‘clinically insignificant’ prostate cancer into its invasive form is still unclear, and it is believed that chronic inflammation may play its role, as proposed by De Marzo in 1999. However, there is no clear opinion on the subject of existence of dependencies between changes of the inflammatory type and PCa.Material and methodsThe st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Inflammation is very common within the prostate, as there are about 10% male adults with prostatitis ( 19 , 20 ). Several studies including a recent study found increased prostate cancer risk with a history of prostatitis and sexually transmitted diseases (relative risk = 1.30 and 1.43; 95% confidence interval: 1.10–1.54 and 1.07–1.91, respectively) ( 21 ).…”
Section: Inflammation and Prostate Cancermentioning
confidence: 99%
“…Inflammation is very common within the prostate, as there are about 10% male adults with prostatitis ( 19 , 20 ). Several studies including a recent study found increased prostate cancer risk with a history of prostatitis and sexually transmitted diseases (relative risk = 1.30 and 1.43; 95% confidence interval: 1.10–1.54 and 1.07–1.91, respectively) ( 21 ).…”
Section: Inflammation and Prostate Cancermentioning
confidence: 99%
“…The incidence of HG–PIN among patients subjected to biopsy due to cancer suspicion ranges from 1.5% to around 16% [610]. In meta–analysis of a number of studies, Epstein and Bostwick calculated the mean risk of diagnosing cancer during second biopsy in patients in whom HG–PIN was diagnosed on first biopsy to be 18.1% and 30%, respectively [11, 12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a positive link between clinical history of prostatitis and increased relative risk of prostate cancer has been documented among 70,000 North American men (6). Chronic inflammation is frequently identified in prostate biopsies, radical prostatectomy specimens and tissue resected from benign prostatic hyperplasia (7,8). A number of possible etiological factors have been proposed in the development of chronic inflammation in the prostate, including dietary imbalances, exposure to environmental pollutants, alterations in testosterone:estrogen ratio, pathogen infection, race or genetic alterations (912).…”
Section: Introductionmentioning
confidence: 99%